“Compare But Not to Compare”: Kajian Perbandingan Hukum di Indonesia - Ratno Lukito (Fakultas Hukum Universitas Jambi, 2022)
Discussing the study of comparative law in Indonesia, this paper is interested in focusing on the issue of why comparative law studies are declining both in quantity and quality. Using Charles Tilly’s theory of social history, this paper concludes that comparative law studies in Indonesia are currently in a stagnant position and fewer people are concerned with the quality of this academic study. This paper reveals that the comparative law that began during the Dutch Rechtshoogeschool in Batavia in 1924 basically did not develop until the present day. Both in terms of epistemology, subject of the study, postulate to method and approach illustrate how comparative law studies have stagnated when compared to the development of this study abroad. Comparative law in Indonesia is only focused on substantive studies without paying attention to this scientific development on the epistemological and methodological side. Improvements can thus be proposed in dealing with this situation, namely by increasing the number of sources of writing and discussion of comparative law from outside, especially those in English, and making this comparative study a core science in legal studies. Abstrak Membahas kajian perbandingan hukum di Indonesia, tulisan ini tertarik untuk memfokuskan diri pada persoalan mengapa kajian perbandingan hukum semakin merosot baik kuantitas maupun kualitasnya. Dengan menggunakan teori sejarah sosial dari Charles Tilly, tulisan ini sampai pada kesimpulan bahwa kajian perbandingan hukum di Indonesia saat ini pada posisi yang mandeg dan semakin sedikit orang yang perhatian dengan mutu dari kajian akademik ini. Tulisan ini mengungkap bahwa perbandingan hukum yang dimulai sejak masa Rechtshoogeschool Belanda di Batavia tahun 1924 pada dasarnya tidak mengalami perkembangan hingga masa sekarang. Baik sisi epistemology, subject of the study, postulate hingga method and approach menggambarkan betapa kajian perbandingan hukum itu mengalami stagnasi bila dibandingkan dengan perkembangan kajian ini di luar negeri. Perbandingan hukum di Indonesia hanya terpusat pada kajian substantive saja tanpa memperhatikan perkembangan keilmuan ini pada sisi epistemologis dan metodologisnya. Perbaikan dengan demikian dapat diusulkan dalam menghadapi situasi ini yaitu dengan semakin memperbanyak sumber tulisan dan bahasan perbandingan hukum dari luar, khususnya yang berbahasa Inggris, dan menjadikan kajian perbandingan ini sebagai ilmu yang inti dalam kajian hukum.